Survival and risk of recurrence of takotsubo syndrome. Issue 14 (8th January 2021) - Lau, Christopher; Chiu, Sarah; Nayak, Rohith; Lin, Bryan; Lee, Ming-Sum
Abstract : Objective: The goal of this study is to evaluate the long-term outcomes of patients with takotsubo syndrome and assess factors associated with death or recurrence. Methods: This is a retrospective population-based cohort study of consecutive patients who presented to an integrated health system in Southern California with takotsubo syndrome between 2006 and 2016. Medical records were manually reviewed to confirm diagnosis and to identify predisposing factors, medication treatment and long-term outcomes. Factors associated with death or recurrent takotsubo syndrome were tested using Cox regression models. Results: Between 2006 and 2016, there were 519 patients with a confirmed diagnosis of takotsubo syndrome. Patients were followed for 5.2 years (IQR 3.0–7.2). During the follow-up period, 39 (7.5%) had recurrent takotsubo syndrome and 84 (16.2%) died. In multivariate modelling, factors associated with higher risk of recurrence or death were age (HR 1.56 per 10-year increase, 95% CI 1.29 to 1.87), male sex (HR 2.52, 95% CI 1.38 to 4.60), diabetes (HR 1.6, 95% CI 1.06 to 2.43), pulmonary disease (HR 2.0, 95% CI 1.37 to 2.91) and chronic kidney disease (HR 1.58, 95% CI 1.01 to 2.47). Treatment with beta-blockers were associated with lower risk of recurrence or death (HR 0.46, 95% CI 0.29 to 0.72). No association was observed between treatment with ACE inhibitors or angiotensin-receptor blockers and recurrence or death (HR 0.92, 95% CI 0.59 to 1.42). Conclusions: Recurrent takotsubo syndrome occurred in a minor subset of patients. Treatment with beta-blocker was associated with higher event-free survival.